PECULIARITIES OF SPEECH USE SITUATIONS IN NATIVE LANGUAGE LESSONS AS A MEANS DEVELOPMENT OF COMMUNICATIVE COMPETENCE JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2022)
The article investigates the problem of studying a native language basing on stududent, speech activity at the elementary level a special aftention is paid to didactic conditions while using comunicative competence skill, of young pupils.